ONLINE NEWPAPER USES AMONG UNIVERSITY STUDENTS - Mat Nayan, Liana; Devarajoo, Aruna Raj; Othman, Siti Suriani; Lee, Kuok Tiung; Nik Hasan, Nik Norma (Journal of Human Capital Development (JHCD), 2016)
Many current studies approved that online newspaper is more popular compared to traditional newspaper, and this trend also included university students as one of the increasing readers. Therefore, this paper discusses the uses of online news among university students in Malaysia by specifically looking at their background which is gender, course of study, and the gratifications gained from the reading. Findings suggested that these three criterias must be considered in order to produce better online newspaper in future. Keywords: online newspaper, student, gender, course, gratification